Detection of Uropathogens and Their Antimicrobial Susceptibility Pattern in Children Attending a Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Medical Microbiology, 2026)
Background: Urinary tract infections (UTIs) are a leading cause of morbidity in children, with rising concern over antimicrobial resistance (AMR) among uropathogens, particularly in resource-limited settings like Bangladesh.Objective: This study was investigated the distribution of uropathogens and their antimicrobial susceptibility patterns in pediatric patients attending a tertiary care hospital in Dhaka. Methodology: This cross-sectional study was conducted from November 2023 to August 2024 in the Department of Microbiology at Bangladesh Shishu Hospital and Institute, Dhaka, Bangladesh. Urine samples from 3,455 pediatric patients suspected of having UTIs were collected and cultured. Pathogen identification and antimicrobial susceptibility testing (AST) were performed using standard microbiological techniques and the Kirby-Bauer disc diffusion method, following CLSI guidelines. Results: Out of 3,455 urine samples, 643(18.6%) showed positive growth, including 494(76.8%) bacterial and 149 (23.2%) fungal isolates. Gram-negative bacteria dominated (72.9%), with Escherichia coli (38.46%) and Klebsiella pneumoniae (10.12%) being the most prevalent. Among Gram-positive isolates, Enterococcus species (26.9%) were predominant. AST revealed widespread multidrug resistance. Escherichia coli showed high resistance to cefixime (100.0%), ampicillin (96.3%), and ciprofloxacin (90.0%), with moderate susceptibility to carbapenems (64.0%). Klebsiella pneumoniae and Pseudomonas aeruginosa also demonstrated significant resistance to third-generation cephalosporins and fluoroquinolones. Enterococcus species exhibited 100% resistance to penicillin but remained largely susceptible to vancomycin.Conclusion: This study underscores an alarming prevalence of multidrug-resistant uropathogens among children with UTIs in Bangladesh. The resistance patterns challenge empirical treatment strategies, highlighting the urgent need for routine AMR surveillance, judicious antibiotic use, and updated local treatment guidelines to ensure effective management of pediatric UTIs.Bangladesh Journal of Medical Microbiology, July 2025;19 (2):107-114